Potensi dan Partisipasi Pemuda Karang Taruna dalam Pengembangan Community Based Tourism di Desa Wisata Kedung Gede - Gagih Pradini; Anisa Putri Kusumaningrusm; Anisa Sesar Yuni Purwati; Putri Aulia Ardani; Asep Syaiful Bahri (Jurnal Ilmiah Wahana Pendidikan, 2023)
In Indonesia, tourism is the sector that contributes most to the economy. For this sector to be successful, expertise is required in managing the available tourism assets. One of them is through developing tourist villages. In developing tourist villages, of course you must implement community-based tourism. Where placing the community as the main actor in the development and management of tourist destinations through empowerment. One of these human resources is youth who are members of Karang Taruna. This research aims to dig deeper into the tourism potential that exists in the Kedung Gede Tourism Village and analyze the level of participation of Karang Taruna youth in developing community-based tourism.